A substitute name for a genus of fossil mantispid (Insecta: Neuroptera: Mesomantispinae) from the Jurassic of Kazakhstan - Jepson, James E.; Khramov, Alexander V.; Ohl, Michael (Zootaxa, 2018)
In a recent paper (Jepson et al., 2018) a new genus of Mesomantispinae from Karatau, Kazakhstan was described. The name given to the genus, Longicollum, is unavailable, because it is preoccupied by a senior homonym, Longicollum Yamaguti, 1935 (Acanthocephala: Pomphorhynchidae). In accordance with Art. 60.1. of the ICZN, we herein propose a replacement name for the genus: Longipronotum nom. nov.